PENERAPAN K-MEANS CLUSTERING PADA PEMILIHAN PROGRAM PRIORITAS DANA DESA - Juhdi Rosadi; Falentino Sembiring; Ati Sulastri; Astrina Natalia Sihite (Jurusan Teknik Informatika, 2020)
AbstractProviding large funds to villages certainly demands a great deal of responsibility for the village government. In managing public funds, a public sector organization is required to be able to provide accountable financial reports. The village head is responsible for the management of village finances and assets. To achieve the effectiveness of village financial management, a decision support system is needed to assist village officials in determining which village programs will be prioritized. This study focuses on village programs that use village fund allocations in Cibatu village, Cisaat District, Sukabumi Regency, West Java. The purpose of this research is to develop a decision support system to determine priority village fund programs using a web-based k-means clustering algorithm. The k-means clustering algorithm can perform the modeling process without supervision (unsupervised) and is one of the methods for grouping data using a partition system. This is in accordance with the desired final result in the form of grouping village work programs into 3 priority levels, namely high priority level in cluster 1, medium priority level in cluster 2 and low priority level in cluster 3. This research was conducted by considering the aspects of urgency and benefits developed. using the PHP version 5 programming language and MySQL version 3.2.1 database. The results of this study are that the village road repair program is included in the high-level priority program in cluster 1, the BUMDES program is included in the medium level priority in cluster 2 and the rainwater storage basin construction program is included in low priority in cluster 3.Keywords : Decision Support System, K-Means Clustering, Village Programs, Village Funds.Pemberian dana desa yang besar tentunya menuntut tanggung jawab yang besar pula bagi pemerintah desa. Suatu organisasi sektor publik dalam mengelola dana masyarakat dituntut harus mampu memberikan laporan keuangan yang bisa dipertanggungjawabkan. Kepala Desa menjadi penanggungjawab pengelolaan keuangan dan aset desa. Untuk mencapai efektifitas pengelolaan keuangan desa maka diperlukan sebuah sistem penunjang keputusan untuk membantu perangkat desa dalam menentukan program desa yang akan di prioritaskan. Penelitian ini berfokus pada program desa yang menggunakan alokasi dana desa di desa Cibatu, Kecamatan Cisaat Kabupaten Sukabumi, Jawa Barat. Tujuan dari penelitian ini adalah membuat sistem penunjang keputusan untuk menentukan program prioritas dana desa yang menggunakan algoritma k-means clustering berbasis web. Algoritma k-means clustering dapat melakukan proses pemodelan tanpa supervisi (unsupervised) dan merupakan salah satu metode yang melakukan pengelompokan data dengan sistem partisi. Ini sesuai dengan hasil akhir yang diinginkan berupa pengelompokan program kerja desa menjadi 3 tingkat proritas, yaitu tingkat prioritas tinggi pada cluster 1, tingkat prioritas sedang pada cluster 2 dan tingkat prioritas rendah pada cluster 3. Penelitian ini dilakukan dengan mempertimbangkan aspek urgensi dan kemanfaatan yang dikembangkan menggunakan bahasa pemrograman PHP versi 5 dan basis data MySQL versi 3.2.1. Hasil dari penelitian ini adalah program perbaikan jalan desa termasuk dalam program prioritas tingkat tinggi pada cluster 1, program BUMDES masuk dalam prioritas tingkat sedang pada cluster 2 dan program pembangunan bak penampung air hujan masuk dalam prioritas rendah pada cluster 3.Kata Kunci : Sistem Penunjang Keputusan, K-Means Clustering, Program Desa, Dana Desa.